Male Breast Cancer in Togo: Imaging and Clinicopathological Findings. (31st August 2020) - Darre, Tchin; Tchaou, Mazamaesso; Djiwa, Toukilnan; Simgban, Panakinao; Amavi, Ayi Kossi; N'Timon, Bidamin; Amadou, Abdoulatif; Bombonne, Mayi; Sama, Bagassam; Amégbor, Koffi; Napo-Koura, Gado
Abstract : Background . Breast cancer in men is a rare condition, often diagnosed late. The purpose of this study was to describe its epidemiological, histopathological, and radiographic aspects in Togo. Materials and Methods . This was a descriptive retrospective study on cases of breast cancer in humans diagnosed histologically at the Laboratory of Anatomy Pathological and Imagery of the University Hospital in Lomé, over a period of 25 years (1995 to 2019). The parameters studied were epidemiological, anatomopathological, and imaging. Results . Eighty-two (82) cases were diagnosed, an annual frequency of 3.28 cases. The mean age was 45 ± 2.5   years ; the range was 27-63 years. The family history of 47 patients (57.32%) was known. Carcinomas represented the predominant histological group with predominantly nonspecific invasive carcinoma (87.5%). These cancers were diagnosed at late stages (75.71% grade II). They were mainly of luminal B profile (38.75%) and associated with mutations of the BRCA2 and BRCA1 genes in 14.63% of the cases. The lesions were classified ACR 5 in 61.5% (11/18). Two cases of breast angiosarcoma were diagnosed by the identification of CD31 markers and factor VIII in immunohistochemistry. Hormone therapy such as tamoxifen was prescribed in all luminal patients (43 patients). Radiotherapy was administered to 15 patients (18.3%), with acute toxicity in 20% of the cases. After a median follow-up of 36 months, the evolution was complete remission in 27 patients (32.93%). Conclusion . Breast cancer in men is rare, often diagnosed late with a poor prognosis.